2015
DOI: 10.1007/s00204-015-1602-x
|View full text |Cite
|
Sign up to set email alerts
|

Application of omics data in regulatory toxicology: report of an international BfR expert workshop

Abstract: Advances in omics techniques and molecular toxicology are necessary to provide new perspectives for regulatory toxicology. By the application of modern molecular techniques, more mechanistic information should be gained to support standard toxicity studies and to contribute to a reduction and refinement of animal experiments required for certain regulatory purposes. The relevance and applicability of data obtained by omics methods to regulatory purposes such as grouping of chemicals, mode of action analysis or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 15 publications
2
21
0
Order By: Relevance
“…Technologies measuring the entirety of gene transcripts, proteins or metabolites in a sample (“omics”) are increasingly used in toxicological research and are discussed to be included into chemical regulatory assessments in the future (Marx-Stoelting et al , 2015). In toxicology, these methods are primarily used to obtain insight into a compound’s mode of action, to group similarly acting compounds or to define new biomarkers (Afshari et al , 2011).…”
mentioning
confidence: 99%
“…Technologies measuring the entirety of gene transcripts, proteins or metabolites in a sample (“omics”) are increasingly used in toxicological research and are discussed to be included into chemical regulatory assessments in the future (Marx-Stoelting et al , 2015). In toxicology, these methods are primarily used to obtain insight into a compound’s mode of action, to group similarly acting compounds or to define new biomarkers (Afshari et al , 2011).…”
mentioning
confidence: 99%
“…At present, a practical application of the Tox21c vision is still far away because of the limited confidence in the new method as the causal link between in vitro data, obtained with new technologies, and adverse effects, tested in vivo , is difficult to establish. The crucial confidence can be reached by simultaneously evaluating phenotypic and molecular endpoints, the latter achievable through in vitro Omics analyses34, considering that the chemical-cell/organ interaction in vivo can be characterized by compensation and adaptive response not necessarily developed in differentiated cell cultures.…”
mentioning
confidence: 99%
“…This is especially related to a lack of method harmonization, standardization and validation of experimental design and data evaluation; in addition, the current definition of adversity of compound‐induced effects impedes the use of omics data in toxicology. Results of a recent workshop on the use of omics technologies in regulatory science have shown that most experts favor an increasing application of omics techniques in toxicological testing in the future, but still feel that additional steps are necessary prior to routine implementation of omics technologies in regulatory test batteries (Marx‐Stoelting et al, ).…”
Section: Discussionmentioning
confidence: 99%